2019
DOI: 10.1155/2019/1493721
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mannitol Content, Regulation of Genes Involved in Mannitol Metabolism, and the Protective Effect of Mannitol onVolvariella volvaceaat Low Temperature

Abstract: The mechanism of autolysis of Volvariella volvacea (V. volvacea) at low temperature has not been fully explained. As mannitol is among the most important osmotic adjustment substances in fungal resistance, this study sampled mycelia of strains V23 and VH3 treated at 0°C for 0, 2, 4, 8, and 10 h to analyze changes in intracellular mannitol content by high-performance anion chromatography with pulsed amperometric detection (HAPEC-PAD). Reverse transcription quantitative PCR (RT-qPCR) analysis was applied to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…First, because they affect the taste of edible mushrooms (by enhancing the sensation of sweet taste) and because the amount of sugar is an important indicator of storage and preservation conditions [ 31 , 32 ]. In addition, mannitol, the most abundant sugar in most mushrooms, plays an important role in regulating osmotic pressure in cells and removing RONS [ 33 ]. For example, Zhao et al [ 33 ] showed that under stress conditions such as low temperature, the synthesis of mannitol was inhibited at the initial stage of Volvariella volvacea growth.…”
Section: Discussionmentioning
confidence: 99%
“…First, because they affect the taste of edible mushrooms (by enhancing the sensation of sweet taste) and because the amount of sugar is an important indicator of storage and preservation conditions [ 31 , 32 ]. In addition, mannitol, the most abundant sugar in most mushrooms, plays an important role in regulating osmotic pressure in cells and removing RONS [ 33 ]. For example, Zhao et al [ 33 ] showed that under stress conditions such as low temperature, the synthesis of mannitol was inhibited at the initial stage of Volvariella volvacea growth.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature plays a decisive role in the growth, storage and quality of V. volvacea ( Zhao et al, 2018 , 2019a ). V. volvacea is not resistant to low temperature, and its mycelia easily undergo autolysis, causing the fruiting bodies to wilt, become liquefied, turn brown, and rot.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, low temperatures below 15°C can negatively impact its growth while causing chilling damage to its fruiting body, and routine storage temperatures (4°C) will cause V. volvacea cryogenic autolysis ( Bao et al, 2013 ). Therefore, V. volvacea cannot be stored at low temperatures like other edible mushrooms, which makes it strain degradation particularly serious ( Zhao et al, 2019 ). Regular subculturing is a commonly applied approach to preserve and rejuvenate various fungal species ( Ayala-Zermeno et al, 2017 ), but excessive subculturing may also induce the biosynthesis of toxins, DNA methylation and chromosome remodeling as shown in Cordyceps militaris ( Yin et al, 2017 ; Xin et al, 2019 ), thereby leading to strain degradation that hinders industrial applications.…”
Section: Introductionmentioning
confidence: 99%